Description of a new intertidal genus Zeahalorhadinus (Coleoptera: Staphylinidae: Aleocharinae) from New Zealand and discussion of its systematic position - Yoo, In-Seong; Ahn, Kee-Jeong (Zootaxa, 2026)
Zeahalorhadinus Yoo & Ahn, gen. nov. is described based on the new species discovered along the coasts of New Zealand. Zeahalorhadinus nunni Yoo & Ahn, sp. nov. is described with illustrations of diagnostic characters. Based on the galea bearing several long setae only on mesal surface from middle to apex, the lacinia with setae on mesal surface, as well as the shape of apical lobe of paramere and the internal sclerites of the median lobe of the aedeagus, the new genus is hypothesized to be a member of the tribe Liparocephalini. Zeahalorhadinus Yoo & Ahn, gen. nov. can be distinguished from related genera by the combination of the following characters: all antennomeres elongate; labrum semicircular with truncate anterior margin, bearing more than 80 setae; ligula very long; mentum with anterior margin deeply emarginate and anterolateral region triangular; elytra distinctly wider than pronotum; and female tergite X with prolonged posterior margin. A comparison table of the new genus with related liparocephaline genera is also provided.